2017
DOI: 10.1080/20786190.2016.1272247
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety symptoms and substance use amongst sex workers attending a non-governmental organisation in KwaZulu-Natal, South Africa

Abstract: Background: Sex work is a high-risk occupation for mental health problems as sex workers are vulnerable to high rates of violence, sexual coercion, stigma and HIV. Aim: To determine the prevalence of depressive and anxiety symptoms and substance use in sex workers.Method: A crosssectional questionnaire survey of all men and women attending the Sisonke health initiative, a non-profit non-governmental organisation (NGO), for sex workers was conducted over three months. A socio-demographic questionnaire, the Self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
1
16
2
Order By: Relevance
“…The prevalence of depression amongst FSWs in Soweto was also higher than those documented in South Africa, with more than two thirds of FSW in Soweto suffering from depression as compared with 4.9% in the total adult population [ 17 ]. While the prevalence of depression in our study was slightly lower than that recorded amongst SWs in KwaZulu Natal (66.3% versus 78.4%) [ 9 ], we note that the KwaZulu Natal study drew from a subset of SWs who were already attending a support group which may have biased the sample. Our findings are almost 10% higher than those found amongst young women in an informal settlement in South Africa [ 18 ].…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…The prevalence of depression amongst FSWs in Soweto was also higher than those documented in South Africa, with more than two thirds of FSW in Soweto suffering from depression as compared with 4.9% in the total adult population [ 17 ]. While the prevalence of depression in our study was slightly lower than that recorded amongst SWs in KwaZulu Natal (66.3% versus 78.4%) [ 9 ], we note that the KwaZulu Natal study drew from a subset of SWs who were already attending a support group which may have biased the sample. Our findings are almost 10% higher than those found amongst young women in an informal settlement in South Africa [ 18 ].…”
Section: Discussioncontrasting
confidence: 83%
“…Approaches to healthcare access which are cognizant of the mental health needs of this population, and which are more holistic in nature, may be important to meeting the overall needs of the population. The criminalisation of sex work has been documented to force SWs to conceal their identities [ 9 ], and the negative social views on SW often lead to SWs feeling isolated and to increasing levels of discrimination being enacted by family, community and public protectors such as health and policing officials [ 5 , 54 , 55 ]. Legislative frameworks and policies which not only contradict South Africa’s Constitution, but further the vulnerability of FSWs while stifling their mental health needs, must be revised by the South African Government.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measures of violence varied by timeframe (recent versus ever), typology (physical, sexual, emotional) and perpetrator (client, intimate partner, etc.). Overall, 13 studies reported associations between depression and violence [34,37,39,43,44,46,49,52,53,59,79,83], with 7 studies included in the meta-analyses (S1 Fig). The pooled unadjusted OR of depression and violence experience (ever or recent) is 2.2 (1.4-3.3), p < 0.001 (n = 7 studies), and the pooled unadjusted OR of depression and recent violence experience is 2.3 (1.3-4.2), p = 0.005 (n = 5 studies).…”
Section: Associations Between Mental Health and Other Factorsmentioning
confidence: 99%
“…Polia et al investigated anxiety, depression, and drug use in the female sex workers. Anxiety and depression were reported as 78% and 80% in the female sex workers, respectively (19). The study of Patel et al showed that depression and anxiety were common in the female sex workers and severity of depression had a significant relationship with violence, disease, and income level (20).…”
Section: Discussionmentioning
confidence: 99%